Antimicrobial efficacy of moringa seed extracts against some postharvest disease pathogens of tomato - . Ibrahim, Tamadur; Salama, Abdelmoneim; Zahran, Eldur (المجلة الزراعية; مجلد 17 عدد 1 (2019), 2019)
Moringa tree has an impressive range of medicinal uses and high nutritional value. The present study deals with the antimicrobial activities of the ethanolic, petroleum ether and aqueous extracts of moringa seeds in controlling some bacteria and fungi and improving postharvest handling of tomato fruits. A sample of 100g of moringa seed powder was extracted successively with petroleum ether and also with ethanol using a Soxhlet apparatus for about four hours with petroleum ether and eight hours with ethanol. Solvents were then evaporated; extracts were left till complete drying. The petroleum ether extract (oil) produced 34.9 ml and the ethanol extract 14.5 g. Various concentrations of seed extracts of moringa (10%, 20%, 30% and 50%) were prepared and evaluated, using a randomized complete block design,  for their antimicrobial efficacy against five species of fungi, namely ( Natrassia mangifera , Fusarium oxysporum , Aspergillus niger , Alternaria alternata and Metarhizium anisoplae ) and three species of bacteria ( Bacillus subtilis , Actinomycetes sp . and Erwinia caratovora ). The ethanolic extract showed a strong antibacterial activity against Actinomycetes sp. and fungicidal activity against F. oxysporum . The aqueous extract presented strong antibacterial activity against B. subtilis and strong antifungal activity against A . niger ,  but the ethanol extract did not show any activity against A . niger and M . anisoplae .  All seed extracts, irrespective of their types, in different concentrations, inhibited the growth of all microbes to varying degrees except petroleum ether extract. The inhibition zone increased gradually with the increase of extract concentration. Tomato fruits were treated with moringa aqueous extract coatings with wax in order to preserve quality and enhance shelf life during storage. Weight loss of uncoated and coated samples was determined throughout storage  at 10 o C and 37 o C for 10 days. The four experimental coatings were wax, wax mixed with 10 ml of crude aqueous extract of moringa, crude extract only and untreated tomatoes.  Moringa extract was effective in extending the shelf-life of treated tomato fruits when compared to the untreated, in the following order:  Wax, moringa extract and untreated control. شجرة  المورينقا ذات قيمة غذائية وطبية عالية.  هدفت هذه الدراسة لمعرفة مدى كفاءة مستخلصات بذور المورينقا باستخدام الكحول الإيثلى, والأثير البترولي والماء في مكافحة البكتيريا والفطريات وتحسين معاملات ما بعد الحصاد لثمار الطماطم. أخذت 100 جرام  من مسحوق بذور المورينقا, وتم الاستخلاص بجهاز سوكسلت أولاً بالبتروليم إيثر لمدة أربعة ساعات ثم الإيثانول لمدة ثمانية ساعات وتم تبخير المذيبات بتعريضها  للهواء.  وكان الناتج من المستخلص 34.94 مل للأثيرالبترولي و 14.47جرام للإيثانول.  أعدت تركيزات مختلفة من المستخلصات وكانت كالآتى (10%، 20%، 30%، 50%) لمعرفة كفاءتها لوقف نشاط خمسة انواع من الفطريات وهى :  Natrassia mangiefra و  Fusarium oxysporum Aspergillus niger    و    Alternaria alternata و Metarhizium anisoplae   وثلاثة انواع من البكتيريا هي Bacillus subtili , Actinomycetes sp. و Erwinia caratovora . مستخلص الكحول الإيثيلى اظهر فعالية كبيرة كمضاد بكتيرى ضد Actinomycetes sp . وتأثيراً كبيراً ضد فطر F.  oxysporum بينما كان للمستخلص المائي تأثير كبير في وقف نشاط  B. subtilis وأكثر كفاءة ضد A.   niger مقارنة بالكحول الإيثيلى والأثير البترولي التي لا يوجد لها تأثير M.   anisoplae و A.   niger   .  ازدادت مسافة التثبيط بزيادة نسبة التركيز للمستخلص تدريجياً. وفى تجربة اخرى تم استخدام المستخلص المائي للمورينقا مع شمع النحل لتغليف ثمار الطماطم وتخزينها في درجة حرارة 10 و37 درجة مئوية لمدة 10 أيام وذلك لمعرفة تأثير مستخلص بذور المورينقا لزيادة فترة صلاحية ثمار الطماطم وإطالة فترة التخزين مع المحافظة على الجودة.  وفى الأربع معاملات (شمع النحل و مستخلص المورينقا واضافة الشمع مع 10مل من المستخلص والثمار غير المعاملة)  كان  مستخلص المورينقا مع شمع النحل أكثر كفاءة في المحافظة على وزن ثمار الطماطم وتقليل تعرضها للعفن وتليها المعاملة بالشمع ثم مستخلص المورينقا مقارنة بالثمار غير المعاملة.